Evaluating Alternatives for Communicating About Food Risk - Ann Fisher; Robert King; Donald J. Epp; J Lynne Brown; Audrey N. Maretzki (Journal of Applied Communications, 1994)
This article describes the development and preliminary evaluation of model materials designed as one-step in helping consumers understand how scientists assess food risk, how that information is used in food safety policy decisions and what individuals can do to protect themselves from residual risks.